2018
DOI: 10.3389/fped.2018.00053
|View full text |Cite
|
Sign up to set email alerts
|

Poor Compliance with Sepsis Guidelines in a Tertiary Care Children’s Hospital Emergency Room

Abstract: ObjectivesThis study aimed to assess factors related to adherence to the Pediatric Advanced Life Support guidelines for severe sepsis and septic shock in an emergency room (ER) of a tertiary care children’s hospital.MethodsThis was a retrospective, observational study of children (0–18 years old) in The Children’s Hospital of San Antonio ER over 1 year with the International Consensus Definition Codes, version-9 (ICD-9) diagnostic codes for “severe sepsis” and “shocks.” Patients in the adherent group were thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Previous studies evaluating adherence to practice guidelines have shown similar data. Our median time to administer antibiotics was 105 min (IQR: 65-185.5 min), while the reported median times from Boston Children's Hospital, Stollery Children's Hospital, Children's Hospital of San Antonio, and Children's Hospital of Philadelphia were 96, 115, 135, and 140 min, respectively (11,13,14,25).…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies evaluating adherence to practice guidelines have shown similar data. Our median time to administer antibiotics was 105 min (IQR: 65-185.5 min), while the reported median times from Boston Children's Hospital, Stollery Children's Hospital, Children's Hospital of San Antonio, and Children's Hospital of Philadelphia were 96, 115, 135, and 140 min, respectively (11,13,14,25).…”
Section: Discussionmentioning
confidence: 76%
“…Even after recognition of shock states, lack of knowledge of fluid resuscitation guidelines and technical limitation of fluid delivery often delay adequate resuscitation 1,2,11,15 . The LifeFlow device serves as technique that appears to offer speed, efficiency and control of volume infused and as a resource to overcome the barrier of fluid delivery in shock states.…”
Section: Discussionmentioning
confidence: 99%
“…Studies based on these guidelines show that earlier fluid delivery directed at reversal of shock reversal leads to decreased morbidity 7-9 , mortality 2,7,[9][10][11][12] , and hospital length of stay (LOS) 9, [11][12][13] . Unfortunately, timely fluid delivery is often not achieved due to the technical challenges of obtaining adequate vascular access and delivering fluid boluses quickly in patients with shock or hypotension 11,[14][15][16] . Current methods of fluid bolus delivery in the pediatric emergency care setting include infusion pumps, gravity drip, pressure bags, rapid infusers, and the push-pull syringe technique 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Children with decompensated shock (prolonged capillary refill plus hypotension) are at the highest risk, with over 30% mortality 1. Earlier fluid delivery targeted at shock reversal results in decreased morbidity,13 mortality,1,38 and hospital length of stay (LOS) 3,7,912. For example, in a prospective cohort study evaluating adherence with guideline recommendations for fluid resuscitation in pediatric septic shock, patients for whom all aspects of the protocol were met had a 57% shorter hospital LOS 9.…”
Section: Introductionmentioning
confidence: 99%
“…This method also carries the risk of air embolism 17. Infusion pumps deliver a maximum rate of 1,000 mL/hr and can achieve 60 mL/kg over 15 mins only in patients weighing <4 kg, but are still commonly used as a method of fluid bolus delivery 9,12. With PPT and DRT, providers may be able to achieve the guideline-recommended rates of infusion,17,18 but these methods are complex and labor-intensive, and both techniques may introduce bacterial contamination into the sterile stopcock 1922.…”
Section: Introductionmentioning
confidence: 99%